«In my actions, I had that one purpose to observe the benefit of the Fatherland…»: investigatory case of governor K. K. Leshern on abuses in the Russian army provision supply in 1812–1813 - Lukashevich, Andrei M. (Journal of the Belarusian State University. History, 2023)
The article reveals the problem of provisions of Russian troops in the Western theater of operations in 1812–1813, through the prism of the investigative case, which was conducted against the Vitebsk civil governor K. K. Leshern. The special attention is given to the mechanism of provisioning in wartime and the role of the field general-proviantmeister, civilian governors, and the Provision Department of the War Ministry of the Russian Empire in this process. The activity of K. K. Leshern in providing provisions in August – November 1812 to the troops of the 1st separate corps of Count P. Kh. Wittgenstein, who operated in the Vitebsk province, is showed. The author analyses in detail the stages of the investigative case of K. K. Leshern (accusations of the Provision Department of the War Ministry of the Russian Empire, explanatory notes of the governor, the results of investigations in the 5th department of the Governing Senate and the State Council of the Russian Empire, materials of additional investigations). It is concluded that abuses in the Provision Department of the War Ministry of the Russian Empire became possible due to miscalculations in the preparation of the rear support of the army on the eve of the war of 1812, and errors made in the supply of troops in wartime, as well as due to the lack of proper control over the expenditure of the Provision Department of the War Ministry of the Russian Empire. It is noted that the persons responsible for abuses in the food supply of the Russian army never received the proper punishment, and the damage caused to the treasury was not compensated by them.
Keywords: civil governor; Belarusian-Lithuanian region; Vitebsk province; K. K. Leshern; War Ministry of the Russian Empire; Provision Department of the War Ministry of the Russian Empire; abuse; commissions of inquiry; State Council of the Russian Empire; Governing Senate